2022
DOI: 10.3390/jcm11206100
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Body Weight and Nutritional Status in Gastric Cancer Patients Enhances the Benefit of Nivolumab Therapy

Abstract: Nivolumab improves overall survival (OS) in patients with advanced gastric cancer (AGC) refractory to at least two previous chemotherapy regimens. We investigated whether changes in body weight and nutrition from first-line chemotherapy to nivolumab affected its efficacy. The correlation between weight change and nutritional status up to the start of nivolumab treatment and OS and progression-free survival (PFS) after starting nivolumab treatment was determined. Nutritional status was examined using the C-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“… 34 Additionally, early intervention to maintain body weight and nutritional status may improve the efficacy of immune checkpoint inhibitors in patients with gastric cancer. 35 Our observations partially align with this report, showing that peridiagnosis weight gain is protective for survival. However, weight gain, especially significant weight gain, 34 can also be a risk factor for OS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 34 Additionally, early intervention to maintain body weight and nutritional status may improve the efficacy of immune checkpoint inhibitors in patients with gastric cancer. 35 Our observations partially align with this report, showing that peridiagnosis weight gain is protective for survival. However, weight gain, especially significant weight gain, 34 can also be a risk factor for OS.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study showed that patients with prediagnosis or postdiagnosis weight gain generally have better outcomes compared with those who experienced weight loss 34 . Additionally, early intervention to maintain body weight and nutritional status may improve the efficacy of immune checkpoint inhibitors in patients with gastric cancer 35 . Our observations partially align with this report, showing that peridiagnosis weight gain is protective for survival.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, a retrospective multi-center study of 97 patients with unresectable or recurrent GC who received nivolumab showed that the median OS was significantly shorter in the group with high changes in CAR from first-line chemotherapy (ΔCAR) than in the group with low ΔCAR (4.5 months vs. 9.4 months, p = 0.002). On multivariate analysis, low ΔCAR was an independent prognostic factor of OS (HR, 0.67; 95% CI, 0.35–0.91, p = 0.02) [ 19 ]. Considering the clinical application of CAR in patients with mGC/EGJC treated with FTD/TPI, using CAR as a prognostic predictor for patients with mGC/EGJC may be a factor in the decision to transition to the next line of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Peri-treatment inflammatory and nutritional status are attracting attention as prognostic factors for patients with cancer [ 16 , 17 ]. Several studies have shown that the C-reactive protein/serum albumin ratio (CAR), which reflects the host’s inflammatory and nutritional status, is a useful prognostic marker in pre-treatment blood testing [ 18 , 19 ]. However, the quest to identify prognostic factors in patients with mGC/GEJC treated with FTD/TPI remain insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, change in CAR after chemoradiation therapy were a prognostic factor (hazard ratio: 5.1842, p = 0.0036). Moreover, Ikoma et al evaluated the clinical impact of change in CAR in 97 gastric cancer patients who received immune checkpoint inhibitor therapy [17]. They found that patients with low change in CAR (≤ 0.01) during immune checkpoint inhibitor therapy had better survival than those with high change in CAR (> 0.01).…”
Section: Discussionmentioning
confidence: 99%